Analisis Cemaran Plumbum (Pb) pada Manisan Buah Kaleng Menggunakan Spektrofotometri Serapan Atom - Anggraini, Deby Ayu; Suharsih, Suharsih; Parinduri, Junaidi (Mahesa Research Center, 2026)
Indonesia is a country with abundant tropical fruit production; therefore, fruit processing into preserved products such as candied fruit is widely carried out to extend shelf life. One form of processed fruit product is candied fruit packaged in cans. However, canned packaging has the potential to cause heavy metal migration into food products. This study aimed to determine the level of lead (Pb) contamination in canned candied rambutan, peach, and lychee. This research employed a quantitative descriptive approach with analysis using the Atomic Absorption Spectrophotometry (AAS) method. The samples consisted of canned candied rambutan, peach, and lychee obtained from supermarkets in the Kutai Kartanegara area. The samples were digested through an ashing process at 500°C and subsequently analyzed using AAS at a wavelength of 324.8 nm. The results showed that all samples contained Pb at relatively low levels. The Pb concentration in candied rambutan ranged from 0.0014–0.0015 mg/kg, in candied peach was 0.0015 mg/kg, and in candied lychee ranged from 0.0016–0.0017 mg/kg. These values were below the maximum permissible limit for heavy metal contamination established by the Indonesian Food and Drug Authority (BPOM), which is 0.1 mg/kg. Therefore, the analyzed canned candied fruit products are considered safe for consumption based on the Pb contamination parameter.